The Effect of Variation Composition of Wheat (Triticum asetivum L.) Grist to Moisture Content and Ash Content of Wheat Flour - Laeliocattleya, Rosalina Ariesta; Wijaya, Jessica (Jurnal Ilmu Pangan dan Hasil Pertanian, 2018)
The aim of this study is to determine how the influence of wheat grist composition variation on Â Australian variety (A) and Russian variety (B) on misture content and ash content of wheat flour. Determination of moisture content and ash content based on Near Infrared Spectroscopy principle. Moisture content of wheat flour on a grist composition 40% A: 60% B was 14.53%, and moisture content of 60% A: 40% B was 14.08%. Variation of wheat grist composition showed a significant different effect (P 0,05) to moisture content of wheat flour. The ash content of flour in grist composition 40% A: 60% B was 0,68%, while grist 60% A: 40% B was 0,66%. Variation of wheat grist composition showed a significant different effect (P 0,05) to the ash content of wheat flour. This is related to the conditions of wheat cultivation and the characteristics of milling wheat.